Effect of Fe on microstructure and properties of AlCoCrFexNi (x=1.5, 2.5) high entropy alloy coatings prepared by laser cladding. (April 2020) - Zhang, G.J.; Tian, Q.W.; Yin, K.X.; Niu, S.Q.; Wu, M.H.; Wang, W.W.; Wang, Y.N.; Huang, J.C.
Abstract: In this study, low-cost AlCoCrFex Ni (x = 1.5, 2.5) high entropy alloy (HEA) coatings were prepared by laser cladding and their microstructural evolutions, mechanical properties and wear behaviors were investigated. Both Fe–Cr rich disordered BCC(A2) phase and Al–Ni rich ordered BCC(B2) phase were identified in these coatings. At x = 1.5, the coating consisted of B2 matrix and nano-scale A2 precipitates. While, at x = 2.5, A2 matrix with B2 precipitates formed. CALPHAD revealed that addition of Fe changed the solidification sequence of coatings, and was beneficial to the formation of A2 phase, resulting in different A2/B2 morphologies. AlCoCrFe2.5 Ni coating exhibited higher strength and better wear resistance, due to the strengthening effect of B2 precipitates was stronger. It was found that the properties of coatings could be improved by regulating the A2/B2 morphology. Moreover, increasing Fe content while maintaining a morphology of A2 matrix with B2 precipitates was a strategy to design high strength HEA coatings. Highlights: Low-cost AlCoCrFex Ni HEA coatings were prepared by laser cladding. The addition of Fe resulted in different A2/B2 morphologies. AlCoCrFe2.5 Ni coating with A2 matrix and B2 particles exhibited better mechanical properties. The properties of coatings could be improved by regulating the A2/B2 morphology.